Porous thin films towards bridging the material gap in heterogeneous catalysis - Dubey, Anjani; Kolekar, Sadhu K.; Gnanakumar, Edwin S.; Roy, Kanak; Vinod, C. P.; Gopinath, Chinnakonda S. (Catalysis, Structure & Reactivity, 2016)
An attempt has been made to bridge the material gap, existing between ideal single crystals and real-world powder nanocatalyst employed in surface science and heterogeneous catalysis, respectively. Simple wet chemical method (sol–gel and spin-coating deposition) has been applied to make continuous Ce1 − xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (~40 nm) and smooth surface characteristics. Uniform thickness and surface smoothness of the films over a large area was supported by a variety of measurements. Molecular beam (MB) studies of O2 adsorption on CZ surfaces reveals the oxygen storage capacity (OSC), and sticking coefficient increases from 400 to 800 K. Porous nature of Ce-rich CZ compositions enhances O2 adsorption and OSC, predominantly due to O-diffusion and redox nature, even at 400 K. A good correlation exists between MB measurements made on CZ films for oxygen adsorption, and OSC, and ambient pressure CO oxidation on powder form of CZ; this demonstrates the large potential to bridge the material gap. CZ was particularly chosen as a model system for the present studies, since it has been well-studied and a correlation between surface science properties made on thin films and catalysis on powder CZ materials could be a litmus test. Ambient catalysis on ceria-zirconia nanocatalyst correlates well with surface properties measured through molecular beam on thinfilm and close the material gap.